2020
DOI: 10.1107/s2059798319016747
|View full text |Cite
|
Sign up to set email alerts
|

The thrombospondin module 1 domain of the matricellular protein CCN3 shows an atypical disulfide pattern and incomplete CWR layers

Abstract: The members of the CCN (Cyr61/CTGF/Nov) family are a group of matricellular regulatory proteins that are essential to a wide range of functional pathways in cell signalling. Through interacting with extracellular matrix components and growth factors via one of their four domains, the CCN proteins are involved in critical biological processes such as angiogenesis, cell proliferation, bone development, fibrogenesis and tumorigenesis. Here, the crystal structure of the thrombospondin module 1 (TSP1) domain of CCN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…It contains both ‘CSXXCG’ sequence and six cysteines. In TSP1 domain, Trp206, Ser218, Arg220, Gln233 and Arg235 are 100% conserved across the CCN family proteins 43 , 44 . It was reported that TSP1 domain of CTGF could bind with exon 7-coded region of VEGF165 and negatively regulate the angiogenic activity of vascular endothelial growth factor (VEGF).…”
Section: Structure Of Ctgfmentioning
confidence: 99%
“…It contains both ‘CSXXCG’ sequence and six cysteines. In TSP1 domain, Trp206, Ser218, Arg220, Gln233 and Arg235 are 100% conserved across the CCN family proteins 43 , 44 . It was reported that TSP1 domain of CTGF could bind with exon 7-coded region of VEGF165 and negatively regulate the angiogenic activity of vascular endothelial growth factor (VEGF).…”
Section: Structure Of Ctgfmentioning
confidence: 99%
“…Briefly, a fusion protein with signal peptide for secretion at the amino-terminal end and human albumin appended at the carboxyl-terminal end of the TSP1 domain (Alb-CCN5(III)) was expressed in CHO cells and purified from the cell culture media by sequential affinity chromatography and size-exclusion chromatography. Based on the extraordinary high degree of structural conservation of TSP1 homology domains among CCN proteins and report of the crystal structure of the TSP1 domain of CCN3 ( 8 ), we also made recombinant fusion protein of the TSP1 domain of CCN3 (Alb-CCN3(III)) configured similar to Alb-CCN5(III). As shown by the concentration-effect studies in Figure 1 B , Alb-CCN5(III) and Alb-CCN3(III) reduced phospho-AKT (Ser473) levels in A549 cells with similar efficacy and potency (IC 50 15.3 μg/ml and 6.8 μg/ml with 95% Confidence Intervals: 2.8–81.8 μg/ml and 4.2–10.8 μg/ml for Alb-CCN5(III) and Alb-CCN3(III), respectively).…”
Section: Resultsmentioning
confidence: 99%
“…TSP1 domains have been reported to exert functions through binding of many different membrane proteins or through binding of other proteins in the extracellular matrix. Among documented binding interactions are integrins, CD36, latent TGF-β, VEGF (vascular endothelial growth factor), collagen, fibronectin, and heparin sulfate–containing proteoglycans ( 8 , 48 , 49 , 50 , 51 , 52 , 53 ) (for review, see refs ( 54 , 55 )). As to CCN proteins, the TSP1 domain of CCN2 has been reported to bind VEGF 165 and sequester VEGF 165 from its receptors ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations